Mechanistic Modeling of Maternal Lymphoid and Fetal Plasma Antiretroviral Exposure During the Third Trimester - Shenkoya, Babajide; Atoyebi, Shakir; Eniayewu, Ibrahim; Akinloye, Abdulafeez; Olagunju, Adeniyi (Frontiers in Pediatrics, 2021)
Pregnancy-induced changes in plasma pharmacokinetics of antiretroviral (ARV) drugs is well established. Current knowledge of the extent of ARV exposure in lymphoid tissues of pregnant women and the fetal compartment is limited due to their inaccessibility. Inadequate distribution of ARVs into important HIV reservoirs like lymphoid tissues during pregnancy may constitute a barrier to adequate virological suppression and increase the risk of mother-to-child transmission. The present study describes the pharmacokinetics of three ARVs (efavirenz, dolutegravir and rilpivirine) in lymphoid tissues and the fetal plasma compartment during pregnancy using a validated materno-fetal physiologically-based pharmacokinetic model (m-f-PBPK). Lymphatic and fetal compartment were integrated into our previously validated adult PBPK model. Physiological and drug disposition processes were described using ordinary differential equations. Essential pharmacokinetic parameters, including Cmax, Cmin, and AUC(0-24) at steady state were computed in maternal lymph and fetal plasma using the concentration-time data obtained. Model predictions were validated with available clinical data, using an acceptance criteria of 1 – 2 absolute average folds error. Model predictions were within 1.08 – 1.99 absolute average fold difference of published data for all the three drugs. Maternal lymph concentrations 24h post dose exceeded the reported minimum effective concentration (MEC) for efavirenz (11,514 ng/ml vs 800 ng/ml) and rilpivirine (118.8 ng/ml vs 50 ng/ml), but was substantially lower for dolutegravir. In addition, predicted maternal lymph-to-plasma AUC ratios vary considerably between these drugs (6.431 – efavirenz, 0.016 – dolutegravir, 1.717 – rilpivirine). Furthermore, fetal plasma-to-maternal plasma AUC ratios were 0.59 for efavirenz, 0.78 for dolutegravir, and 0.57 for rilpivirine. Longer dose forgiveness was observed for efavirenz in maternal lymph (126h), and dolutegravir in fetal plasma (42h). The predicted low lymphoid tissue penetration of dolutegravir appears to be significantly counterbalanced by its extended dose forgiveness and adequate fetal compartment exposure. Hence, it is unlikely to be a predictor of maternal virological failure or mother-to-child transmission risks. Model predictions align with recommendations of no dose adjustment despite moderate changes in exposure during pregnancy for these drugs. This is an important new application of PBPK modelling strategy to evaluate the adequacy of drug exposure in an otherwise inaccessible compartment.